ISOLATION AND ANTIBACTERIAL TEST OF GARLIC OIL - A. T. Karossi; M. Hanafi; L. Sutedja (Research Center for Chemistry - LIPI, 1993)
Garlic oil is known to have medicinal effect on hypertension, heart desease, anemia and various infections. The active principles are reported to be allicin, diallil disulfide, allilpropyl disulfide, scorduun, selenium and germanium in addition to the presence of anticoagulant, anuhaemolytic and arulthrombotic agents. The methods applied for isolation and other conditions during the isolation affect the yield or the compositions of the oil, for instance with steam distillation the allicin will decompose whereas extraction at room temperature will yield oil with allicin as the main component. In the present study isolation was conducted by extraction with ethylacetate or ethanol and the oil obtained was tested for their antibacterial capacity. Tests against Staphylococcus aureus, Bacillus cereus and Escherichia coli indicated that the isolated oil were active. On the other hand, commercial garlic extract (KGE) and garlic oil capsule (GOC) gave negative test. This may have been due to either insufficient concentration. of the biologically active component present in the commercial drugs or different method of extraction process. investigation with thin layer chromatography (TLC) of the drugs On silica gel plate ustngn-hexane and ethyl acetate as eluents showed six components in the GOC and none in KGE whereas for the isolated oil 13 components were identified with iodine vapour. Although the oils indicated antibacterial activity, it is somehow less active compared with oxytetracycline which is used as reference.